αv Integrins combine with LC3 and atg5 to regulate Toll-like receptor signalling in B cells - Mridu Acharya (Nature Portfolio, 2016)
Integrins can regulate antigen-specific and innate immune receptor signalling, thereby affecting immune cell function. Here the authors show that avß3 integrin controls Toll-like receptor (TLR) signalling by regulating its trafficking to limit TLR-mediated B-cell proliferation and antibody production.